2008
DOI: 10.1007/s00127-008-0344-y
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Finnish acute psychiatric hospital patients

Abstract: Mortality among Finnish psychiatric acute hospital patients is considerably higher than in general population. Excessive alcohol consumption plays a major role in causing excess deaths that could be potentially avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 38 publications
6
20
1
Order By: Relevance
“…[12] and Honkonen, et al . [13] Our findings are consistent with earlier studies[313] in the context that mortality among men was higher. More than half of the deceased had been admitted for a week or even more recently, a period that can be considered as a crucial period for the subjects.…”
Section: Discussionsupporting
confidence: 93%
“…[12] and Honkonen, et al . [13] Our findings are consistent with earlier studies[313] in the context that mortality among men was higher. More than half of the deceased had been admitted for a week or even more recently, a period that can be considered as a crucial period for the subjects.…”
Section: Discussionsupporting
confidence: 93%
“…This paper has identified an overall trend that corresponds to earlier findings, that patients with some psychiatric diagnosis have an excess mortality compared to the general population, and that concurrent substance abuse increases the mortality 4,11,14 . An explanation for the observed increase in mortality rates might be insufficient awareness of the psychical morbidity in psychiatric patients 4 .…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, there is a body of scientific evidence showing that subjects with both drug and psychiatric problems constitute a higher risk group, with vulnerability for mortality and morbidity compared with the general population [29]. Also in this study we found, especially among women, high SRR for mortality among those with a history of hospitalisation with an alcohol or drug abuse diagnosis [29]. Bartu et al reported that opiate abusers had higher all-cause and drug-related mortality risks compared with amphetamine users [10].…”
Section: Discussionmentioning
confidence: 98%